Head Start educators’ professional well-being and their turnover intentions: the moderating role of perceived workplace discrimination - Zhao, Xiangyu; Byun, Sooyeon; Jeon, Lieny (Frontiers in Psychology, 2025)
High turnover is a critical challenge for Head Start programs. This study aims to understand how professional well-being and workplace factors are related to turnover intentions within Head Start educators. Utilizing hierarchical linear modeling with a sample of 304 educators, the study examined how positive aspects (i.e., compassion satisfaction) and negative aspects (i.e., secondary traumatic stress and emotional exhaustion) of professional well-being, along with perceived workplace discrimination, are associated with their turnover intentions (i.e., intention to leave the profession, program, or position). The findings demonstrated that compassion satisfaction, emotional exhaustion, and workplace discrimination were significantly associated with turnover intentions. The study also descriptively examined the specific reasons behind these intentions, which included poor benefits and compensation, classroom management stress, and a lack of advancement opportunities. These findings suggest the need for interventions and policies to enhance educators’ professional well-being, address workplace discrimination, and improve working conditions to retain qualified Head Start educators.